UTILIZATION OF THE FLOTATION METHOD TO IMPROVE OPTIMIZATION OF COAL QUALITY - Taskum Setiadi (Jurnal Scientia, 2023)
The relatively high sulfur content of Indonesian coal, which can cause burner damage and environmental pollution, is one of its weaknesses. One technique to reduce the concentration of inorganic sulfur is flotation. In the flotation device, research was carried out on the use of the flotation method to improve the optimization of coal quality. The research method used in this research is literature or literature. The coal used in this study is coal originating from the Sulawesi region. The research results stated that the ideal coal desulfurization is 0.07%, according to the results of coal desulphurization experiments using the flotation method for particle size.